Prebiotic and Probiotic Regulation of Bone Health: Role of the Intestine and its Microbiome - McCabe, Laura (Curr Osteoporos Rep, 2015)
Recent advances in our understanding of how the intestinal microbiome contributes to health and disease have generated great interest in developing strategies for modulating the abundance of microbes and/or their activity to improve overall human health and prevent pathologies such as osteoporosis. Bone is an organ that the gut has long been known to regulate through absorption of calcium, the key bone mineral. However, it is clear that modulation of the gut and its microbiome can affect bone density and strength in a variety of animal models (zebra fish, rodents, chicken) and humans. This is demonstrated in studies ablating the microbiome through antibiotic treatment or using germ-free mouse conditions as well as in studies modulating the microbiome activity and composition through prebiotic and/or probiotic treatment. This review will discuss recent developments in this new and exciting area.